Client knowledge, attitudes and practices to cervical screening in Mitchell's Plain, Cape Town, South Africa - Daries, Vanessa Cheryl (Adolescent Health Research Institute, 2023)
Background: Cervical cancer is a common cause of death among women in developing countries, including South Africa. In 2000, the South African National Department of Health introduced the national cervical cancer screening policy, which states that every woman is entitled to three free Papanicolaou (Pap) smears in her lifetime, at 1 0-year intervals starting at the age of 30 years. A number of studies have indicated that the uptake of cervical cancer screening is dependent on the targeted population's knowledge, attitudes and practices (KAP) related to health-seeking behaviours. The aim of the study is to determine the baseline KAP to Pap smears and cervical cancer of women aged 25 years and older in Mitchell's Plain, Western Cape Province. Methods: A cross-sectional survey was undertaken among clients attending primary health care facilities in the Mitchell's Plain district, Cape Town, Western Cape Province. The study population consisted of women aged 25 years and older who presented at the public health care facilities in Mitchell's Plain between 1 April and 31 July 2002 and who consented to participate in the study. The data were analysed using the STAT A version 8 statistical package. Results: A total of 445 women were interviewed, most of whom were above the age of 30 years (72%), married (68%) and unemployed (68%). Ninety-five per cent said they had heard of a Pap smear; however, when asked what part of the body was examined during a Pap smear, only 4% correctly answered. Only 13% of the women knew that a Pap smear was a test for cancer of the cervix, although 52% recognised it as a test for cancer. Of the women interviewed, 73% had heard of cancer of the cervix. A total of 78% of women had had a Pap smear. The results indicated no significant association between ever hearing of a pap smear and the following predictors: age, educational level, marital status, pregnancy and the use of contraception. Women who were significantly more likely to have had a Pap smear included: older women, those who were in a relationship, owned a radio, were employed, had ever been pregnant or had heard of a Pap smear before. Main sources of information regarding Pap smears were reported to be posters (17%) and the radio (16%). Conclusions: The data suggest that although a very high proportion of the women (95%) had heard of Pap smears, a smaller proportion (78%) had actually had a Pap smear. This study showed that there were missed opportunities that the health workers could possibly have utilised to encourage women in the targeted age group to have a Pap smear while at the health facilities for reasons other than reproductive health. Women who had not been afforded the opportunity to have a Pap smear by the health provider reported a great interest in having a Pap smear, showing willingness to improve their health if afforded the opportunity. In order to reduce the high morbidity and mortality from cervical cancer in South Africa, very large numbers of women in the target age group need to be recruited to the screening programme. To be able to achieve an increase in the cervical cancer screening uptake, huge efforts have to be made to actively recruit women who are within reach of the health services, particularly any women who present at the health facilities.